Towards Economic Democracy and Social Justice: Profit Sharing, Co-Determination, and Employee Ownership - Felix FitzRoy; Michael A. Nolan (Institute of Labor Economics (IZA), 2020)
Modern economies deprive workers of natural democratic rights and any share of the surplus they produce, with most of the benefits of growth appropriated by capital owners. Worker wellbeing and job satisfaction are ignored unless they contribute directly to profitability, while precarious employment and underemployment, with stagnant or declining real wages, have persisted over four decades, despite recent low official unemployment. For economic democracy and social justice, we propose redistributive tax and welfare reform, extended codetermination, subsidised profit sharing and employee buyouts.
Keywords: H; P; 330; economic democracy; participation; co-determination; profit sharing; employee ownership